SZ_GERICHTE STK 2019 4 vom 26. November 2019 , versuchte Nötigung, versuchte Anstiftung zu falschem Zeugnis - SZ Gerichte (2019)
versuchte Nötigung, versuchte Anstiftung zu falschem Zeugnis | Strafgesetzbuch